Simplified ARCHITECT microfluidic chip through a dual-flip strategy enables stable and versatile tumoroid formation combined with label-free quantitative proteomic analysis. (8th April 2021) - Feng, Danni; Lv, Junwei; Abdulla, Aynur; Xu, Jianwei; Sang, Xiao; Wang, Liping; Liu, Wenjia; Lou, Jiatao; Bo, Zhao; Ding, Xianting
Abstract: Recent years, microfluidic three-dimensional (3D) tumor culture technique has made great progress in tumor microenvironment simulation and drug screening. Meanwhile, as their functionality and complexity increase, it is more difficult for current chip models to selectively collect specific-layer cells from tumoroids for further analysis. Moreover, a simplified and robust method for tumoroid formation with highly consistent size and repeatable 3D morphology is relatively ncessary. Here, we report an ARCHITECT (ARtificial CHIp for Tumor Enables Confocal Topography observation) chip, through a dual-flip strategy to implement straightforward tumoroid establishment. This platform guarantees stable batch-to-batch tumoroids formation and allows high resolution confocal imaging. Moreover, an initial cell density as low as 65 cells per chamber is efficient to deliver a tumoroid. With this ARCHITECT chip, different-layer cells of interest could be collected from tumoroid for label-free quantitative (LFQ) proteomic analysis. For application demonstration, we mainly verified this platform for lung carcinoma (A549) tumoroid construction and proteomic analysis at out layer. Our data indicate that the out-layer cells of A549 tumoroid show extensively distinct proteomic expressions compared to two-dimensional cultured A549 cells. The up-regulated proteins are mainly related to tumorigenicity, proliferation and metastasis. And the differentially expressed proteins are mainly relevant to lipid metabolism pathway which is essential to tumor progression and proliferation. This platform provides a simplified yet robust technique to connect microfluidic tumoroid construction and LFQ proteomic analysis. The simplicity of this technique should open the way to numerous applications such as discovering the innovative targets for cancer treatment, and studying the mophological and proteomic heterogeneity of different-layer cells across the tumoroid.